Transcatheter arterial embolization for hemorrhage after gynecologic hysterectomy: a multicenter study. (June 2022) - Chen, Cheng Shi; Cho, Young-Jong; Shin, Ji Hoon; Kim, Jeong Ho; Park, Suyoung; Jeon, Gyeong Sik; Ibrahim, Alrashidi; Li, Hai-Liang; Jeong, Boryeong
Background: Transcatheter arterial embolization (TAE) is not common for hemorrhagic complications after gynecologic hysterectomy. Purpose: To evaluate the effectiveness and safety of TAE for hemorrhage after hysterectomy for gynecologic diseases. Material and Methods: This is a retrospective, multicenter study, which investigated 11 patients (median age = 45 years) who underwent TAE for hemorrhage after gynecologic hysterectomy between 2004 and 2020. Results: The median interval between surgery and angiography was one day (range = 0–82 days). Hemodynamic instability and massive transfusion were present in 6 (54.5%) and 4 (36.4%) patients, respectively. CT scans (n = 7) showed contrast extravasation (n = 5), pseudoaneurysm (n = 1), or both (n = 1). On angiography, the bleeding arteries were the anterior division branches of the internal iliac artery (IIA) (n = 6), posterior division branch (lateral sacral artery, n = 1), and inferior epigastric artery (n = 1) in eight patients with active bleeding. In the remaining three patients, angiographic staining without active bleeding foci was observed at the vaginal stump, and the feeders for staining were all anterior division branches of the IIA. Technical and clinical success rates were 100% and 90.9% (10/11), respectively. In one patient, active bleeding focus was successfully embolized on angiography, but surgical hemostasis was performed for suspected bleeding on exploratory laparotomy. Postembolization syndrome occurred in one patient. Conclusions: TAE is effective and safe for hemorrhage after hysterectomy for gynecologic diseases. Angiographic findings are primarily active bleeding, but angiographic staining is not uncommon. A bleeding focus is possible in any branch of the IIA, as well as the arteries supplying the abdominal wall.